Investigation of Antidiabetic Effect of Pistacia atlantica Leaves by Activity-Guided Fractionation and Phytochemical Content Analysis by LC-QTOF-MS - Pekacar, Sultan; Deliorman Orhan, Didem (Frontiers in Pharmacology, 2022)
In this study, the antidiabetic, antiobesity, antioxidant, and antihyperlipidemic effects potential of Pistacia atlantica Desf. leaves were evaluated by in vitro methods. The effects of the leaves of the plant on pancreatic lipase, pancreatic cholesterol esterase, and PTP1B enzymes were investigated for the first time and it was observed that leaf methanol extract (IC50: 123.67 ± 0.40 µg/mL) and n-hexane sub-extract (IC50: 61.03 ± 0.11 µg/mL) had much stronger effects on pancreatic cholesterol esterase enzyme than simvastatin (IC50: 142.30 ± 5.67 µg/mL). The methanolic extract of P. atlantica leaves exerted strong inhibitory effect on the enzymes (α-amylase and α-glucosidase) effective on carbohydrate digestion. It was thought that the methanol extract could provide significant benefits against oxidative stress in diabetes mellitus since it showed antioxidant activities (DPPH radical scavenging activity and reducing power) as strong as reference compounds (ascorbic acid and quercetin). Qualitative and quantitative analyzes of rutin (0.328 ± 0.000 g/100 g dry extract), methyl gallate (5.245 ± 0.014 g/100 g dry extract), quercetin-3-O-glucoside (0.231 ± 0.000 g/100 g dry extract), and gallic acid (0.528 ± 0.127 g/100 g dry extract) in methanol extract were performed by RP-HPLC. The phytochemical content of the active sub-fraction obtained from the leaf methanol extract by activity-guided fractionation and column chromatography studies was characterized by LC-QTOF-MS. The presence of trigalloylglucose, digalloylglucose, and methyl gallate in the G6 coded sub-fraction obtained by chromatographic techniques from the ethyl acetate sub-extract, which has the highest inhibitory effect on α-amylase and α-glucosidase enzymes, was determined by LC-QTOF-MS. In addition to the G5 coded subfraction, a strong α-glucosidase enzyme inhibitory activity was also observed in the G6 coded sub-fraction, and methyl gallate, methyl digallate, 2''-O-galloyl-quercetin-3-O-hexoside, and myricetin-3-O-hexoside were identified in this sub-fraction. This study displayed that the methanol extract of P. atlantica leaves could be a potential source for bioactive compounds with antidiabetic effects by showing inhibitory effects on enzymes involved in carbohydrate digestion.